O racismo e a sub-representação dos negros na alta liderança do mundo corporativo: 1850 a 1990 - Vicente, Raphael de Lima (2019)
Introduction - The slave system profoundly marked the formation of Brazilian society. In Brazil, the skin becomes a social operator of access or prohibitions, a determining legacy of impossibilities for blacks and whites, and the process of miscegenation was a fallacy to make blacks invisible and exclude the labor market. Objective – To examine how the heritage of slavery in the state of São Paulo contributes directly to the formation and conditions of the labor market in the twentieth century. Methods – The State of São Paulo was defined as a region to be observed. The spacetime was defined between 1850 and 1990, the important moments of economic transition and models of labor use. Results – The state of São Paulo is clearly the most advanced case of this transformation, and when one tries to recap São Paulo's experience of economic growth and development on a national scale, Sao Paulo's experience of race becomes even more important as a possible prognosis of things to come. Racist society admitted the black as a slave; brought to European free labor, alleged that blacks had no “mindset” to integrate with modern modes of production. Conclusion – The extremely efficient slave-black inheritance, in the shape of a black exclusion cycle, radiates and consolidates structures and hierarchies, which among its effects make it extremely difficult for blacks to arrive and remain in the command posts of the labor market